Role of Therapeutic Plasma Exchange in Improving Inflammatory and Thrombotic Biomarker Levels in Covid 19 Patients: Experience from Tertiary care Hospital of Balochistan - Bashir, Saima (International Journal of Pathology, 2022)
Introduction: Two proposed molecular mechanisms associated with Covid-19 induced lung injury are microthrombogenesis and inflammatory cytokine release. To reduce the inflammatory reaction is the key to reduce mortality and morbidity. Due to the lack of specific treatment, various treatment modalities including Plasmapheresis have been applied. Objective: Our objective is to evaluate the Role of Therapeutic plasma exchange (TPE) in improving Inflammatory and thrombotic biomarker levels in Covid-19 patients. Material and Methods: It is a Prospective longitudinal study, conducted at Combined Military Hospital Quetta from Jan to Dec 2021.All the PCR Confirmed Covid-19 positive patients who received Plasmapheresis as therapy during the duration of the study were included. Parameters under study were Total leukocyte count (TLC), C Reactive proteins (CRP), Ferritin, Lactate dehydrogenase (LD), Procalcitonin (PCT), IL-6, and Alanine transaminase (ALT).Samples were collected before and after every session. 40 ml /kg bodyweight of the patient was exchanged with FFPs derived from the blood of healthy donors. Biochemical parameters were analyzed on automated C501 and Cobas e411 analyzers .D-dimers were performed on manual latex kit. Data were analyzed using SPSS 21 Result: Data distribution was checked using Kolmogorov- Smirnov test. Categorical variables were expressed as frequencies while for continuous variables mean and SD was calculated. Wilcoxon signed-rank test is used for comparing the levels of different biochemical and hematological markers on different days before and after Plasmapheresis. Levels of IL-6, PCT, CRP, and Ferritin were high before and after Plasmapheresis. Their levels reduced significantly within 07 days (p < 0.05).There was no significant difference between Total leukocyte and platelet count. Conclusion: Therapeutic plasma exchange is an avenue for future clinical trials. It can be utilize as a treatment in patients with raised cytokine and thrombotic markers levels